The Role of Athletic Self-efficacy and Athletic Perfectionism in Predicting Athletic Performance of Gazi University Student Athletes - Temel Çakiroğlu (Journal of Educational Issues, 2024)
Athletic performance is the physical and mental effort of an individual or a sports team to win and defeat the other person or team. The aim of this study was to investigate the role of athletic self-efficacy and athletic perfectionism in predicting athletic performance of athletic students of Gazi University. The method of this study is descriptive and correlational. The statistical population includes all student athletes of Gazi University, which is 360 people. To determine the sample size, Cochran’s sample size estimation formula was used and the number of samples was equivalent to 186 individuals selected by simple random sampling method. Standard questionnaires on athletic self-efficacy, athletic perfectionism and athletic performance were used to collect data. The data were analyzed using SPSS 24 software. Descriptive statistics for quantitative variables were presented as mean and standard deviation. The regression coefficient was used to determine the role of athletic self-efficacy and perfectionism in predicting students’ athletic performance. Athletic self-efficacy and athletic perfectionism play an important role in predicting athletic performance of student athletes. Athletic self-efficacy and athletic perfectionism predicted 0.54 and 0.46 (p < 0.05) of changes in athletic performance, respectively. As athletic self-efficacy and athletic perfectionism increase, so does athletic performance in student athletes. Coaches are advised to pay attention not only to physical condition but also to psychological characteristics and especially to indicators of perfectionism and self-efficacy when selecting players.